Does Airbnb offer hedonic or utilitarian products? An experimental analysis of motivations to use Airbnb. Issue 22 (17th November 2022) - Volz, Jonas; Volgger, Michael
ABSTRACT: There has been an ongoing debate regarding motivations to book Airbnb accommodations. One position highlights the role of experiences and an alternative position emphasizes the equal relevance of costs and practical amenities. This experimental research indirectly examines these motivations by analysing the impact of affective and cognitive advertising on attitude and behavioural intentions to book with Airbnb. It also compares it with the advertising effectiveness in a strongly hedonic accommodation product such as boutique hotels. A randomized online experiment assigned 525 participants to one out of four text ads and analysed their responses using 2-way ANOVA. Study findings show no significant differences in effectiveness between emotional and rational ads in the case of Airbnb. This contrasts with the control group of boutique hotels where results confirm emotional appeals to be more effective. These findings indicate that Airbnb is chosen for a hybrid mix of utilitarian and hedonic consumption motivations disconfirming purely experiential interpretations.